Performance Evaluation of Routing Protocols for multimedia transmission over Mobile Ad hoc Network - Christos Bouras; Vaggelis Kapoulas; Apostolos Gkamas; G Kioumourtzis; George Adam; Nikos Tavoularis (4th Joint IFIP Wireless and Mobile Networks Conference, Toulouse, France, 2011)
Abstract— Mobile ad hoc networks (MANETs) are becoming more essential to wireless communications due to growing popularity of mobile devices. The integration of mobile ad hoc devices inside vehicles has led to another type of networks, called Vehicular Ad hoc Networks (VANETs) which are also becoming important. These networks require specialized routing protocols due to their ad hoc nature. The performance of these protocols has been tested for the case of general traffic but not in respect with to multimedia traffic and especially video transmission. In this paper we conduct a number of simulations in order to evaluate the performance of three of the most popular routing protocols for MANETs and VANETs, namely AODV, DSR and OLSR, for different number of simultaneous video transmissions. We use the packet delivery ratio, the end-to-end delay, the packet delay variation (jitter) and the routing overhead as evaluation metrics. The results indicate that the DSR protocol outperforms AODV and OLSR in terms of end-to-end delay and packet delay variation and seems to be the most efficient routing protocol when multimedia traffic and especially video traffic is considered.